Road Safety in Kenya: A Case Study of Nairobi Southern Bypass (UCA-2) Road - Akinyi, M.; Kabubo, C. K.; Winja, M. M. O. (Engineering, Technology & Applied Science Research, 2020)
The fundamental objective of transportation is to ensure that people and goods are safely and effectively moved from one place to another. Analyzing the design consistency is one of the ways in which the road’s safety can be maintained or enhanced. In order to obtain a balance in highway design, all the geometric components should, along with being economical functional, be designed to provide safety at speeds likely to occur under ordinary conditions. Distinguishing and treating any geometric inconsistency on an expressway can altogether enhance its safety outcome.